2004
DOI: 10.1177/107327480401100107
|View full text |Cite
|
Sign up to set email alerts
|

5-Fluorouracil–Induced Coronary Vasospasm

Abstract: This observation supports the vasospastic hypothesis for 5-FU-induced angina. Although rare, this type of cardiotoxicity with 5-FU is a potentially lethal side effect. Therapy with 5-FU should be discontinued and patients should be promptly treated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 11 publications
0
33
0
3
Order By: Relevance
“…Finally, because mammalian cells lack an analogous UPRT enzyme (28), the capacity of LdUPRT to recognize cytotoxic nucleobase analogs offers a potential therapeutic strategy by which cytotoxic uracil derivatives could be selectively incorporated into the parasite nucleotide pool without impacting the human host. 5-Fluorouracil and 4-thiouracil, however, are not prospective candidates as pro-drugs for which LdUPRT activation is required because 5-fluorouracil, an anti-neoplastic agent employed pervasively in the treatment of gastrointestinal cancers (29), exhibits unacceptable toxicity toward mammalian cells (30), whereas 4-thiouracil is nontoxic toward wild type L. donovani (Fig. 9A).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, because mammalian cells lack an analogous UPRT enzyme (28), the capacity of LdUPRT to recognize cytotoxic nucleobase analogs offers a potential therapeutic strategy by which cytotoxic uracil derivatives could be selectively incorporated into the parasite nucleotide pool without impacting the human host. 5-Fluorouracil and 4-thiouracil, however, are not prospective candidates as pro-drugs for which LdUPRT activation is required because 5-fluorouracil, an anti-neoplastic agent employed pervasively in the treatment of gastrointestinal cancers (29), exhibits unacceptable toxicity toward mammalian cells (30), whereas 4-thiouracil is nontoxic toward wild type L. donovani (Fig. 9A).…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound and angiographic studies demonstrate both coronary artery and brachial artery vasospasm following 5-FU infusion [21][22][23]. Prior case reports reveal disease-free coronary arteries on angiography [24].…”
Section: Coronary Vasospasmmentioning
confidence: 99%
“…Vasospasm is a reasonable mechanism, since it would explain reports of the effi cacy of vasodilating drugs given prophylactically to patients who experienced a previous episode of chest pain during 5-FU treatment 5,6 . Angina pectoris, acute myocardial infarction, congestive heart failure, cardiomyopathy, myopericarditis, ventricular and supraventricular tachycardia, prolonged QT interval, sudden death, cardiogenic shock and coronary dissection are counted among cardiotoxic eff ects of 5-FU 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Th e therapy was discontinued and the patient was transferred to our intensive care unit because the electrocardiogram (ECG) showed ischemic changes. Th e fi rst ECG showed ST elevation and peaked T waves in D I-III , aVL, aVF and V [2][3][4][5][6] derivations as well as reciprocal changes in aVR and V I ( Figure 1). Detailed history revealed that a coronary angiography revealing non-pathological fi ndings was performed two weeks ago as a result of a similar clinical picture in another center.…”
Section: Case Presentationmentioning
confidence: 99%